2021
DOI: 10.3389/fonc.2021.762288
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin/Adriamycin Monotherapy or Plus Ifosfamide in First-Line Treatment for Advanced Soft Tissue Sarcoma: A Pooled Analysis of Randomized Trials

Abstract: BackgroundDoxorubicin/Adriamycin (ADM) alone or combined with ifosfamide (IFO) (AI) is available for previously untreated advanced soft tissue sarcoma (ASTS). However, the clinical choice between them remains controversial. In this pooled analysis, we comprehensively compared the efficacy and tolerability of AI versus ADM in patients with ASTS.MethodsPubMed, Web of Science, EMBASE, and Cochrane Library were systematically searched from inception to April 14, 2021. Eligible studies were randomized clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In contrast to IFO (ORR: RR 1.37, 95% CI 0.94–1.99, P = .10), [ 7 ] NFO seems more effective when combined with DOX in elevating the response rates in ASTS. However, up to now, no direct comparison studies between IFO and NFO have been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to IFO (ORR: RR 1.37, 95% CI 0.94–1.99, P = .10), [ 7 ] NFO seems more effective when combined with DOX in elevating the response rates in ASTS. However, up to now, no direct comparison studies between IFO and NFO have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…[3] However, several studies have demonstrated that the addition of IFO to DOX failed to improve the overall responses and survival outcomes in ASTS patients. [4][5][6][7] In clinical practice for ASTS, DOX plus IFO chemotherapy is still recommended as a first-line option, especially for younger age (<65 years old) and well-performance (ECOG 0-1) patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ORR of doxorubicin plus ifosfamide in treating STSs is 21%–38%, with a median PFS of 5.6–11 months ( Table 1 ). Although the combination of doxorubicin and ifosfamide improves the ORR and median PFS compared with doxorubicin alone, it does not improve the median OS ( Table 1 ) and instead increases hematological toxicity such as leucopenia and anemia ( Maurel et al, 2009 ; Judson et al, 2014 ; Wang et al, 2021 ). Therefore, recently, this combined regimen is not recommended as a first-line chemotherapy for advanced STSs but is only recommended for preoperative neoadjuvant chemotherapy of high-risk STSs ( Judson et al, 2014 ; Weiss et al, 2020 ).…”
Section: Efficacy Of Different Drugs In Stssmentioning
confidence: 99%
“…The ORR of the doxorubicin plus ifosfamide in treating STS is 21%–38%, and the median PFS is 5.6–11 months ( Table 1 ; Table 2 ). Compared with doxorubicin or ifosfamide alone, the combination of doxorubicin and ifosfamide increases the ORR and median PFS but does not improve the median OS in patients with advanced STSs ( Table 1 ; Table 2 ) ( Maurel et al, 2009 ; Judson et al, 2014 ; Wang et al, 2021 ). Currently, this combined regimen is recommended for preoperative neoadjuvant chemotherapy in high-risk STSs ( Judson et al, 2014 ; Weiss et al, 2020 ).…”
Section: Efficacy Of Different Drugs In Stssmentioning
confidence: 99%
“…It also has antibacterial and anti-fungal activities and an excellent safety profile making it worthy for consideration in clinical trials. Wang et al (2021) performed an analysis of 3 open-label randomized phase 2/3 clinical trials with a total of 1,108 previously untreated advanced soft tissue sarcoma patients. The aim of the study was to compare monotherapy with doxorubicin/adriamycin (ADM) alone to ADM combined with ifosfamide (AI).…”
mentioning
confidence: 99%